Validation of the Muscle Dysmorphic Disorder Inventory (MDDI) in Brazilian Women. (June 2022) - Nagata, Jason M.; Junqueira, Alessandra Costa Pereira; Cattle, Chloe J.; Carvalho, Pedro Henrique Berbert de; Bagolin, Vitoria; Murray, Stuart B.; Compte, Emilio J.; Braga Costa, Telma Maria; Almeida, Sebastião de Sousa; Laus, Maria Fernanda
Abstract: Despite high levels of body dissatisfaction and an increasing drive for muscularity among Brazilian women, most of the existing literature on muscle dysmorphia focuses on men and has mainly been conducted in Western and English-speaking regions. As a result, one of the most widely used assessment tools for symptoms of the disorder, the Muscle Dysmorphic Disorder Inventory (MDDI), has not yet been evaluated in Brazilian women—an at-risk population. In the present study, we perform a psychometric evaluation of the Brazilian Portuguese translation of the MDDI in a sample of 515 women. We evaluated the factor structure using a two-step, split-sample exploratory and confirmatory factor analytic approach, which supported the original three-factor structure of the measure. Additionally, we found good internal consistency, convergent validity, and test-retest reliability of the measure. Collectively, these results support the use of the measure in Brazilian women and provide a foundation to expand the literature in this population. Highlights: We validated the Muscle Dysmorphic Disorder Inventory in Brazilian women. Exploratory factor analysis supported three factors in Brazilian women. The internal consistency of the MDDI subscales was supported. There was support for convergent validity of the MDDI subscales. The MDDI can be used to evaluate symptoms of muscle dysmorphia in Brazilian women.